Penatalaksanaan Fisioterapi Pada Kasus Post Operatif Fraktur Patella Sinistra Di RSUD DR. Soehadi Prijonegoro Sragen - Winarni Ningsih, Nutri, Totok Budi Santoso,S.Fis,MPH (2015)
Background : the dissolution of the intregity of bone fractures, usually a result of trauma. Can fracture occurred at the therhold of bone and joints that can also cause joint dislocation. Methods : the intervention given the form of contraction, free active movement, passive involuntary movements, continued to relax, refused active movement, bridging exercise, exercise sitting, standing and walking using kruk. Evaluations include pain, range of movement joints, anthropometry, values and muscle strength increased capacity functional activity. Result : the texable income is as much as 6 therapy times available findings as follows pain assessment silent T1 : 5 be T6 : 3, pain T1 : press : 6 being : T6 : 4, pain motion T1 : 7 being T6 : 5, increase joint range of motion S T1 : 0-7-0 being S T6 : 0-0-45, the findings of oedema equity 2 cm. in crease muscle strength hip flexor T1 : 1 become T6 : 3, hip extensor T1 : 1become T6 : 3, knee flexor T1 : 1 become T6 : 3, knee extensor T1 : 1 become T6 : 3, flexor angkle T1 : 1 become T6 : 3. As well as the improvement of functional ability with ADL indes of T1 : 24 being T6 : 17. Conclucion : therapeutic exercise can reduces pain and spasm of muscules around the knee gastrocnemous sinistra, oedema reducing result incision wound around the knee, increase muscle strength, increase range of motion knee and increase ability functional activity. Keyword : fracture the left patella, therapeutic exercise.